Estratégias utilizadas por colaboradores de nível médio e consultores, para criação e compartilhamento de conhecimento - Bacchi, Victor Alexandre (2014)
This research was developed with the aim of contributing to studies that identify the strategies used by individuals in the creation and sharing of knowledge within organizations process. Using the vision of employees from middle management and external consultants, we intend to identify what are the practices most used by this audience, when inserted in situations conducive to the generation of new knowledge. Moreover, the objective is to identify the forms of personal interaction that these professionals utilize more in the same context. The intention is that this study is not only a tool for reflection, but also a useful tool for organizations to improve their processes and delimit related to the creation and management of knowledge contribution